Tire wear particles in the environment: A critical review on key challenges and future perspectives in fate, risk, and mitigation - Niling Zou; Hongjun Xiao; Gaoju Zou; Dehua Du; Zhen Liu; Shixin Zhang; Jiayue Zhu; Fan Yang; Kaifeng Wang; Anke Du; Yao Chen (Journal of Water Process Engineering, 2026)

Tire wear particles induce a functional trade-off in bioretention systems: Coupled effects on nitrogen removal and greenhouse gas emissions - Gaoju Zou; Niling Zou; Yinghui Tang; Qinyi Wang; Hongjun Xiao; Quanhong Chen; Zhen Liu; Kaifeng Wang; Fan Yang; Huachao Zhao; Yu Qin; Anke Du; et al. (Environmental Research, 2026)

A multi-scale assessment of topographic anisotropy on Land Surface Emissivity and Temperature retrieval over the Yarlung Tsangpo River basin - Hongjun Zhu; Xin Pan; Shanhu Jiang; Xingwang Fan; Kevin Tansey; Zhenwei Wang; Rufat Guluzade; Matthew Payne; Jie Yuan; Suyi Liu; Zi Yang; Yingbao Yang (International Journal of Remote Sensing, 2026)

Interactions and binding mechanisms of soy protein isolate with theasinensin A in different pH conditions by multi-spectroscopy analysis and molecular docking - Haoyu Zhang; Weiqi Xu; Yulu Wang; Xia Fan; Qiankun Guo; Hongjun Liu; Jialu Ao; Tianjin Sun; Muhammad Abid; Xiaoxiong Zeng (Food Chemistry, 2026)

Counter-cation engineering in polyoxovanadate cathodes: Unlocking superior zinc-ion storage stability via NH4+ induced hydrogen bond networks - Tiantian Guan; Chunxi Ren; Kunxuan Li; Yu Zhang; Fan Yang; Lei Wang; Qing Han; Xuejing Qiu; Lingling Xie; Hongjun Chen; Xiaobo Ji; Jianmin Ma; et al. (Chemical Engineering Journal, 2026)

Escalating landscape fire exposure and its deteriorating global equity: Role of associated population changes, socioeconomic levels, and climate changes - Tong Pan; Hongjun Wang; Jiyuan Chen; Zipei Fan; Xuan Song (Science of The Total Environment, 2026)

Efficient preparation and structural characterization of theabrownins from fermented summer green tea with Aspergillus cristatus (MK346334) in submerged fermentation - Jingqian Zheng; Jiayue Fang; Hongjun Liu; Zhiyong Xie; Xia Fan; Guijie Chen; Xiaoxiong Zeng (Food Chemistry, 2025)

Molecular design of polyoxovanadate cathodes for advanced AZIBs: Multielectron redox chemistry and structural engineering - Yu Zhang; Tiantian Guan; Fan Yang; Qing Han; Lingling Xie; Xuejing Qiu; Lei Wang; Hongjun Chen; Yuling Wang; Xiaobo Ji; Limin Zhu; Xiaoyu Cao (Chemical Engineering Journal, 2025)

Preliminary Feasibility Study of Using Hydrogen as a Fuel for an Aquaculture Vessel in Tasmania, Australia - Hongjun Fan; Peggy Shu-Ling Chen; Andrew Harris; Nagi Abdussamie; Evan Mac A. Gray; Irene Penesis; Javad A. Mehr (Journal of Marine Science and Engineering, 2025)
Decarbonising aquaculture support vessels is pivotal to reducing greenhouse gas (GHG) emissions across both the aquaculture and maritime sectors. This study evaluates the technical and economic feasibility of deploying hydrogen as a marine fuel for a 14.95 m net cleaning vessel (NCV) operating in Tasmania, Australia. The analysis retains the vessel’s original layout and subdivision to enable a like-for-like comparison between conventional diesel and hydrogen-based systems. Two options are evaluated: (i) replacing both the main propulsion engines and auxiliary generator sets with hydrogen-based systems—either proton exchange membrane fuel cells (PEMFCs) or internal combustion engines (ICEs); and (ii) replacing only the diesel generator sets with hydrogen power systems. The assessment covers system sizing, onboard hydrogen storage integration, operational constraints, lifecycle cost, and GHG abatement. Option (i) is constrained by the sizes and weights of PEMFC systems and hydrogen-fuelled ICEs, rendering full conversion unfeasible within current spatial and technological limits. Option (ii) is technically feasible: sixteen 700 bar cylinders (131.2 kg H2 total) meet one day of onboard power demand for net-cleaning operations, with bunkering via swap-and-go skids at the berth. The annualised total cost of ownership for the PEMFC systems is 1.98 times that of diesel generator sets, while enabling annual CO2 reductions of 433 t. The findings provide a practical decarbonisation pathway for small- to medium-sized service vessels in niche maritime sectors such as aquaculture, while clarifying near-term trade-offs between cost and emissions.

Multi-perspective analysis of long-term vehicle emissions under intensive policy updates in China - Wentian Xu; Fangyuan Zheng; Zhouzhi Li; Junxia Gao; Hui Tong; Haomiao Niu; Bin Sun; Zhaoyang Fan; Lin Wu; Hongjun Mao (Transportation Research Part D: Transport and Environment, 2025)

Environmental benefit assessment of vehicle electrification in the fuel cycle: A case study of Chengdu - Zhaoyang Fan; Hui Tong; Naixiu Sun; Yangxin Xiong; Xuan Qu; Hongjun Mao; Jianfei Peng (Atmospheric Environment, 2025)

High Yield of Prodigiosin by Serratia marcescens Ka3 Using Additive Huangshui, a Byproduct of Chinese Liquor (Baijiu) - Chuan Wang; Zhongxing Gao; Rui Han; Yaomei Tian; Hongjun Fan; Yuliang Zhang (Current Microbiology, 2025)

Contribution of Vehicular Evaporative S/IVOC emission to SOA formation in China - Zhaoyang Fan; Yajun Wu; Yuwei Xie; Hui Tong; Naixiu Sun; Pengfei Song; Wentian Xu; Yan Liu; Shaojie Song; Hongjun Mao; Jianfei Peng (Atmospheric Environment, 2025)

Impact of flow velocity on growth performance, muscle texture, and nutritional composition in seabass (Lateolabrax maculatus) - Fan Fei; Yingying Fang; Zhiwen Zhu; Xinyu Liu; Ao Li; Jiawen Zhang; Xiaoqiang Gao; Wenyang Li; Hongjun Yang; Wensheng Li; Chuanxin Zhang; Baoliang Liu (Aquaculture International, 2025)

Identification of multiple miRNA-encoded peptide reveals OsmiPEP162a putatively stabilizes OsMIR162 in rice - Jianping Zhou; Rui Zhang; Qinqin Han; Hongjun Yang; Wei Wang; Yibo Wang; Xuelian Zheng; Fan Luo; Guangze Cai; Yong Zhang (Plant Cell Reports, 2025)

Effect of Photoperiod on Nutritional Quality of Muscle and Lipid Metabolism of Litopenaeus vannamei - Yingying Fang; Fan Fei; Fulu Guo; Chengliang Zhu; Xiaoqiang Gao; Wenyang Li; Hongjun Yang; Yan Sun; Chuanxin Zhang; Baoliang Liu (Fishes, 2024)
Photoperiod serves as a significant environmental signal for organisms and plays a critical role in regulating their metabolic processes. This research aimed to investigate the lipid metabolism and nutritional quality of adults Litopenaeus vannamei (wet weight: 11.27 ± 0.73 g, body length: 12.45 ± 0.42 cm) under five photoperiods (0L:24D, 8L:16D, 12L:12D, 16L:8D, and 24L:0D) for 40 days in recirculating water systems (RASs). The 24L:0D group increased lipid metabolism, as indicated by increased lipid metabolism enzyme levels and related gene expression linked to lipogenesis. Additionally, shrimp in the 24L:0D exhibited the highest value of crude fat. The 0L:24D showed a significantly reduced content of crude fat compared with the 8L:16D and 12L:12D. In 24L:0D, the content of total essential amino acids (TEAAs), total hydrolyzed essential amino acids (THEAAs), and total non-essential amino acids (TNEAAs) increased significantly. Similarly, the content of polyunsaturated fatty acids (PUFAs) in 24L:0D was also higher than in other groups. Conversely, 0L:24D resulted in lower metabolic activity and a reduction in PUFA content. In conclusion, prolonging light could benefit shrimp cultivation. This study thoroughly examined the effects of varying photoperiods on muscle quality and lipid metabolism in L. vannamei, providing essential insights for the improvement of indoor aquaculture environments. Provision of light for 24 h improves production but has some adverse effects on animal welfare, so a 16 h light cycle is recommended.

Fractal research on pores in oil and gas reservoirs - Inspirations from over 700 high pressure mercury injection experiments - Xingxing Kong; Hongjun Fan; Tingen Fan; Yufei Gao; Haifeng Wang; Pengfei Mu; Dianshi Xiao (Marine and Petroleum Geology, 2024)

Microplastic transport and ecological risk in coastal intruded aquifers based on a coupled seawater intrusion and microplastic risk assessment model - Guangquan Chen; Yinqiao Zou; Guiyao Xiong; Yancheng Wang; Wenqing Zhao; Xingyong Xu; Xiaobin Zhu; Jichun Wu; Fan Song; Hongjun Yu (Journal of Hazardous Materials, 2024)

Source-to-sink processes and genetic mechanism of progradational and lateral accretion submarine fans in the Qiongdongnan Basin, South China Sea - Congjun Feng; Guozhang Fan; Zhili Yang; Xingzong Yao; Xinglei Song; Weiqiang Li; Hongjun Qu; Qiang Zhang; Xuefeng Wang (Frontiers in Marine Science, 2024)
Submarine fan reservoirs are important accumulation zones for oil, gas, and natural gas hydrates, offering significant potential for hydrocarbon exploration. During the deposition period of the Sanya Formation in the southern part of the Changchang Sag of the Qiongdongnan Basin, a large submarine fan developed. However, the internal structure, source-sink system, and formation mechanism of this fan remain poorly understood, posing significant challenges to exploration in this area. This paper examines the source-to-sink sedimentary processes and deposition of submarine fans, using the Changchang Sag, in the Qiongdongnan Basin in the Northern South China Sea, as an example, which will provide valuable general guidance for deep water oil and gas exploration. Based on the theories of seismic stratigraphy and seismic sedimentology, this paper utilizes techniques such as seismic facies analysis, seismic attribute optimization, paleogeomorphology reconstruction, and source-to-sink sedimentary system analysis to analyze the 3D seismic data of the study area. Research indicates that the Sanya Formation in the Changchang Sag of the Qiongdongnan Basin comprises three depositional units: submarine fan, feeder channel, and Semi-deep marine to deep marine mudstone. The submarine fan is a fan formed by the coupling and convergence of submarine fans sourced from the southwest and southeast. Internally, it is divided into three sub-facies: the proximal fan of the sand-rich submarine fan, the main body of the sand-rich submarine fan lobes, and the distal lobes of the sand-rich submarine fan. The submarine fan sourced from the southwest extends nearly north-south and is primarily fed by sediment transported through three large, banded ancient valleys. The sedimentary filling is characterized by three-phase progradation. The submarine fan sourced from the southeast extends nearly east-west and is primarily fed by sediment transported through a single large, banded ancient valley. The sedimentary filling is characterized by two-phase lateral accumulation. During the deposition period of the Sanya Formation, certain areas of the southern uplift belt were exposed for extended periods and subjected to weathering and erosion. Sediments are transported to large ancient valleys through small supply channels. A large number of sediments were transported to the southern slope of the Changchang sag through the provenance channel system such as large ancient valleys and slope belts and deposited in the center of the sag. These make up a complete system of large ancient uplifts and submarine fan source-to-sink sedimentary systems.The sedimentary model is a lobed submarine fan controlled by semi-restricted ancient valleys and expansive basins.

Review of utilization of bamboo fiber in asphalt modification: Insights into preparation, performance, reinforcement, and challenges - Haibin Li; Songjiang Liu; Fan Yang; Siyu He; Hongjun Jing; Xiaolong Zou; Zhigang Li; Yanping Sheng (Journal of Cleaner Production, 2024)

Spatial heterogeneity plays a vital role in shaping the structure and function of estuarine carbon-fixing bacterial communities - Jianrong Xu; Hongxia Ming; Kaijia Ren; Dongwei Li; Huiling Huang; Jiajie Li; Kuishuang Shao; Hongjun Li; Jingfeng Fan (Marine Environmental Research, 2024)

Exploring Seasonal Variations in Fish Communities: A Study of the Yellow River Estuary and Its Adjacent Waters Using eDNA and Trawl Surveys - Xiaoyang Wang; Fan Li; Fei Shao; Hongjun Song; Na Song; Xiaomin Zhang; Linlin Zhao (Fishes, 2024)
The Yellow River Estuary and its adjacent waters serve as crucial spawning, foraging, and nursery areas for marine organisms, possessing abundant biological resources. Monitoring fish communities provides a baseline for implementing the sustainable utilization of marine resources. In this study, data were collected from 15 spring surface and bottom sites and 17 summer surface sites using eDNA and trawl surveys. The results showed that 37, 40, and 35 fish species were detected using eDNA in the spring (surface and bottom) and summer (surface), respectively, with 38 fish species caught during summer trawling. The dominant species mainly belonged to Engraulidae of Clupeiformes in the spring and Gobiidae of Perciformes in the summer, characterized by smaller-sized, short-lived, and pelagic fish species. The summer surface communities exhibited higher diversity than the spring surface and bottom communities. NMDS analysis revealed a degree of seasonal differences in fish communities and that there may be a lack of vertical stratification in the spring communities. The pH and DO were identified as the key environmental factors affecting the fish community. Additionally, the combination of eDNA and trawl surveys was regarded as a superior survey method. Our study provides valuable information for understanding seasonal fish communities in the Yellow River Estuary and its adjacent waters, contributing to fishery resource management and conservation in the region.

Evaluation indicators for road traffic energy consumption: a review and prospect - Bin Sun; Le Hu; Zhaoyang Fan; Hongjun Mao; Qijun Zhang (Environmental Science and Pollution Research, 2024)

Environmental impacts of potential mining-replacing-import alternative for China in response to the China-Australia coal ban - Zhaoyang Fan; Xin Ju; Hui Tong; Zilu Liang; Naixiu Sun; Hongjun Mao; Jianfei Peng (Journal of Cleaner Production, 2024)

Enhanced management and antifouling performance of a novel NiFe-LDH@MnO2/PVDF hybrid membrane for efficient oily wastewater treatment - Kai Fan; Ning Kong; Jing Ma; Hongjun Lin; Chuanyang Gao; Jinshen Lei; Zihang Zeng; Jun Hu; Juncheng Qi; Liguo Shen (Journal of Environmental Management, 2024)

Seasonal changes driving shifts in microbial community assembly and species coexistence in an urban river - Wangkai Fang; Tingyu Fan; Shun Wang; Xiaokun Yu; Akang Lu; Xingming Wang; Weimin Zhou; Hongjun Yuan; Lei Zhang (Science of The Total Environment, 2023)

Anaerobic biodegradation of azo dye reactive black 5 by a novel strain Shewanella sp. SR1: Pathway and mechanisms - Jiale Liu; Lu Fan; Wenjun Yin; Shusheng Zhang; Xiaomei Su; Hongjun Lin; Haiying Yu; Zhenghai Jiang; Faqian Sun (Journal of Environmental Management, 2023)

Benthic bacterial communities indicate anthropogenic activity footprints in coastal area under long-term marine spatial planning practice - Yi Sun; Hongjun Li; Daixi Liu; Xiaocheng Wang; Quanming Wang; Xiaoyu Cui; Jingfeng Fan (Acta Oceanologica Sinica, 2023)

Anti-ice-pinning superhydrophobic surfaces for extremely low ice adhesion - Ze Tian; Peixun Fan; Dongyu Zhu; Lizhong Wang; Huanyu Zhao; Changhao Chen; Rui Peng; Daizhou Li; Hongjun Zhang; Minlin Zhong (Chemical Engineering Journal, 2023)

Particulate emissions from gasoline vehicles using three different fuel injection technologies - Zongyan Lv; Jianfei Peng; Jinsheng Zhang; Lei Yang; Dongping Guo; Ning Wei; Yajun Wu; Tiange Fang; Ainan Song; Chaoyang Fan; Lin Wu; Qijun Zhang; et al. (Journal of Cleaner Production, 2023)

Clinical, epidemiological, and genotypic characteristics of rotavirus infection in hospitalized infants and young children in Yunnan Province - Hongjun Jiang; Yu Zhang; Xiaoyan Xu; Xiaohan Li; Yi Sun; Xin Fan; Ya Xu; Ting Su; Guiqian Zhang; Ziqin Dian (Archives of Virology, 2023)
Rotaviruses are the most important pathogenic cause of non-bacterial diarrhea in infants and children. Approximately 60% of hospital admissions for acute diarrhea worldwide are caused by rotavirus infection. Rotavirus infection and hospitalization among children in China are a social burden, resulting in economic loss. The prevalence and geographical distribution of rotavirus genotypes is variable, partially due to population migration. Due to the unique geographical conditions and climate in Yunnan Province, several viruses with new genotypes have emerged, and multiple genotypes have become co-epidemic. In this study, rotavirus infection screening and genetic characterization of epidemic strains were performed in 149,492 infants and children admitted to hospitals in six representative prefectures in Yunnan Province between 2019 and 2021. The prevalence of rotavirus infection was 13.39% and was highest in January and lowest in September. G9P[8] was the main epidemic rotavirus genotype. Other epidemic genotypes included G2P[4], G8P[8], G9P[4], G2P[8], G3P[8], G4P[8], G3P[4], and G4P[6]. Phylogenetic analysis revealed that locally epidemic strains were influenced by importation of strains from neighboring provinces and other Asian countries. These findings provide a scientific basis for rotavirus prevention and control and lay a foundation for preliminary studies to establish a rotavirus surveillance network in Yunnan Province.

Effect of quorum quenching on biofouling control and microbial community in membrane bioreactors by Brucella sp. ZJ1 - Rui Wang; Zijing An; Lu Fan; Yan Zhou; Xiaomei Su; Junjie Zhu; Qian Zhang; Chongjun Chen; Hongjun Lin; Faqian Sun (Journal of Environmental Management, 2023)

Flexible dual-functionalized hyaluronic acid hydrogel adhesives formed in situ for rapid hemostasis - Penghui Fan; Qi Dong; Junfeng Yang; Yun Chen; Hongjun Yang; Shaojin Gu; Weilin Xu; Yingshan Zhou (Carbohydrate Polymers, 2023)

Novel mesocellular silica foam supported poly(amidoxime-ethyleneimine) network for fast and highly efficient uranium extraction from seawater - Jiajia Yang; Yun Li; Tian Tian; Haitao Shi; Zia Ahmad; Ningbo Geng; Jing Jin; Yanqiang Huang; Haijun Zhang; Hongjun Fan; Jiping Chen (Chemical Engineering Journal, 2023)

Safe Design of a Hydrogen-Powered Ship: CFD Simulation on Hydrogen Leakage in the Fuel Cell Room - Wenfeng Guan; Ju Chen; Lijian Chen; Jiaolong Cao; Hongjun Fan (Journal of Marine Science and Engineering, 2023)
Adopting proton exchange membrane fuel cells fuelled by hydrogen presents a promising solution for the shipping industry’s deep decarbonisation. However, the potential safety risks associated with hydrogen leakage pose a significant challenge to the development of hydrogen-powered ships. This study examines the safe design principles and leakage risks of the hydrogen gas supply system of China’s first newbuilt hydrogen-powered ship. This study utilises the computational fluid dynamics tool FLACS to analyse the hydrogen dispersion behaviour and concentration distributions in the hydrogen fuel cell room based on the ship’s parameters. This study predicts the flammable gas cloud and time points when gas monitoring points first reach the hydrogen volume concentrations of 0.8% and 1.6% in various leakage scenarios, including four different diameters (1, 3, 5, and 10 mm) and five different directions. This study’s findings indicate that smaller hydrogen pipeline diameters contribute to increased hydrogen safety. Specifically, in the hydrogen fuel cell room, a single-point leakage in a hydrogen pipeline with an inner diameter not exceeding 3 mm eliminates the possibility of flammable gas cloud explosions. Following a 10 mm leakage diameter, the hydrogen concentration in nearly all room positions reaches 4.0% within 6 s of leakage. While the leakage diameter does not impact the location of the monitoring point that first activates the hydrogen leak alarm and triggers an emergency hydrogen supply shutdown, the presence of obstructions near hydrogen detectors and the leakage direction can affect it. These insights provide guidance on the optimal locations for hydrogen detectors in the fuel cell room and the pipeline diameters on hydrogen gas supply systems, which can facilitate the safe design of hydrogen-powered ships.

Engineering metal–organic frameworks (MOFs) based thin-film nanocomposite (TFN) membranes for molecular separation - Die Ling Zhao; Fan Feng; Liguo Shen; Zhengyi Huang; Qipeng Zhao; Hongjun Lin; Tai-Shung Chung (Chemical Engineering Journal, 2023)

A novel process for simultaneous biological nutrient removal and waste activated sludge reduction in one-stage system without aeration - Zhiwei Fan; Wei Zeng; Yuan Jia; Qingan Meng; Hongjun Liu; Hong Liu; Yongzhen Peng (Chemical Engineering Journal, 2023)

Helical configuration channels boost performance in anion exchange membranes - Yang Zhang; Fan Zhang; Yiwen Chen; Lixuan Sun; Chengpeng Wei; Huaqing Zhang; Hongjun Zhang; Bangjiao Ye; Liang Wu; Xiaolin Ge; Tongwen Xu (Chemical Engineering Journal, 2023)

Source apportionment of VOCs based on photochemical loss in summer at a suburban site in Beijing - Yajun Wu; Xiaolong Fan; Yan Liu; Jingqiao Zhang; Han Wang; Luna Sun; Tiange Fang; Hongjun Mao; Jun Hu; Lin Wu; Jianfei Peng; Shulan Wang (Atmospheric Environment, 2023)

A data-driven approach for the measurement and improvement of regional industrial ecological efficiency for carbon peaking and carbon neutralization - Fan Liu; Cuixia Zhang; Yingyan Zhang; Hongjun Liu (Environmental Science and Pollution Research, 2023)

Life Cycle Greenhouse Gas Emission Assessment for Using Alternative Marine Fuels: A Very Large Crude Carrier (VLCC) Case Study - Jinjin Huang; Hongjun Fan; Xiangyang Xu; Zheyu Liu (Journal of Marine Science and Engineering, 2022)
The International Maritime Organization (IMO) has set decarbonisation goals for the shipping industry. As a result, shipowners and operators are preparing to use low- or zero-carbon alternative fuels. The greenhouse gas (GHG) emission performances are fundamental for choosing suitable marine fuels. However, the current regulations adopt tank-to-wake (TTW) emission assessment methods that could misrepresent the total climate impacts of fuels. To better understand the well-to-wake (WTW) GHG emission performances, this work applied the life cycle assessment (LCA) method to a very large crude carrier (VLCC) sailing between the Middle East and China to investigate the emissions. The life cycle GHG emission impacts of using alternative fuels, including liquified natural gas (LNG), methanol, and ammonia, were evaluated and compared with using marine gas oil (MGO). The bunkering site of the VLCC was in Zhoushan port, China. The MGO and LNG were imported from overseas, while methanol and ammonia were produced in China. Four production pathways for methanol and three production pathways for ammonia were examined. The results showed that, compared with MGO, using fossil energy-based methanol and ammonia has no positive effect in terms of annual WTW GHG emissions. The emission reduction effects of fuels ranking from highest to lowest were full solar and battery-based methanol, full solar and battery-based ammonia, and LNG. Because marine ammonia-fuelled engines have not been commercialised, laboratory data were used to evaluate the nitrous oxide (N2O) emissions. The GHG emission reduction potential of ammonia can be exploited more effectively if the N2O emitted from engines is captured and disposed of through after-treatment technologies. This paper discussed three scenarios of N2O emission abatement ratios of 30%, 50%, and 90%. The resulting emission reduction effects showed that using full solar and battery-based ammonia with 90% N2O abatement performs better than using full solar and battery-based methanol. The main innovation of this work is realising the LCA GHG emission assessment for a deep-sea ship.

Genome characterization and comparative analysis among three swimming crab species - Ming Liu; Shanshan Ge; Shivish Bhandari; Chunlei Fan; Yu Jiao; Chunlei Gai; Youhong Wang; Hongjun Liu (Frontiers in Marine Science, 2022)
In this study we sequenced the genomes of three economically important swimming crabs Portunus trituberculatus, Charybdis japonica , and Callinectes sapidus using the next-generation sequencing approach and made a basic assembly. The genomes of the three species are characterized with high heterozygosity (>1.2%) and high repeat content (>50%). Genome comparative analysis revealed 40 long conserved fragments (>5,000 bp) among the three species, most of them are involved in cardiac-related biological process. Relative higher genome similarity was found between P. trituberculatus and C. japonica that are belong to different subfamilies, compared to that between P. trituberculatus and C. sapidus which are from the same subfamily. It is inconsistent with their phylogenetic evolutionary trees inferred from previous mitochondrial DNA coding fragments and a conserved ANK2 protein fragment from this study. We speculated that the high genome similarity between P. trituberculatus and C. japonica might be attributed to their same inhabit range in which the genome is subject to the same environment selection, and the inconsistence between genome similarity and phylogenetic relationship is caused by the different evolutionary rates of coding DNA and non-coding DNA under environment selection.

How habitat heterogeneity shapes bacterial and protistan communities in temperate coastal areas near estuaries - Zelong Zhao; Hongjun Li; Yi Sun; Kuishuang Shao; Xiaocheng Wang; Xindong Ma; Anyi Hu; Haikun Zhang; Jinfeng Fan (Environmental Microbiology, 2022)
Summary In this study, we investigated microbial communities (bacteria and protist) in two coastal areas near the estuaries of the Liaohe (LH) River and Yalujiang (YLJ) River in the Northwestern Pacific Ocean. Due to the existence of Liaodong Peninsula and different levels of urbanization, geographical segregation and significant environmental heterogeneity were observed between these two areas. There were significantly different regional species pools and biogeographic patterns for both bacterial and protistan communities between LH and YLJ coastal areas. Species turnover was the main mechanism driving β‐diversity patterns of both bacterial and protistan communities in each area. In addition, the contributed ratio of nestedness to the β‐diversity patterns was significantly higher for protists compared to bacteria. Variation in regional species pools was found to be the dominant driver of differences of bacterial and protistan communities between the LH and YLJ coastal areas. For a single‐studied area, local community assembly mechanisms, including heterogeneous selection and dispersal limitation, were found to shape the bacterial and protistan communities through calculation of the β‐deviation index. Among them, the relative importance of heterogeneous selection and dispersal limitation on the community assembly varied according to microorganism type and habitat.

Human Error Probability Assessment for LNG Bunkering Based on Fuzzy Bayesian Network-CREAM Model - Hongjun Fan; Hossein Enshaei; Shantha Gamini Jayasinghe (Journal of Marine Science and Engineering, 2022)
Liquified natural gas (LNG) as a marine fuel has gained momentum as the maritime industry moves towards a sustainable future. Since unwanted LNG release may lead to severe consequences, performing quantitative risk assessment (QRA) for LNG bunkering operations has become mandatory according to some regulations. Human error is a main contributor to the risks, and the human error probabilities (HEPs) are essential for inclusion in a QRA. However, HEPs data are unavailable in the LNG bunkering industry so far. Therefore, this study attempts to infer HEPs through on-site safety philosophical factors (SPFs). The cognitive reliability and error analysis method (CREAM) was adopted as a basic model and modified to make it suitable for HEP assessment in LNG bunkering. Nine common performance condition (CPC) indicators were identified based on the fuzzy ranking of 23 SPF indicators (SPFIs). A Bayesian network (BN) was built to simulate the occurrence probabilities of different contextual control modes (COCOMs), and a conditional probability table (CPT) for the COCOM node with 19,683 possible combinations in the BN was developed according to the CREAM’s COCOM matrix. The prior probabilities of CPCs were evaluated using the fuzzy set theory (FST) based on data acquired from an online questionnaire survey. The results showed that the prior HEP for LNG bunkering is 0.009841. This value can be updated based on the re-evaluation of on-site SPFIs for a specific LNG bunkering project to capture the dynamics of HEP. The main innovation of this work is realizing the efficient quantification of HEP for LNG bunkering operations by using the proposed fuzzy BN-CREAM model.

Effect of dietary Bacillus licheniformis on growth, intestinal health, and resistance to nitrite stress in Pacific white shrimp Litopenaeus vannamei - Ying Fan; Xiaolu Wang; Youhong Wang; Haibin Ye; Xiaoqing Yu; Shuxian Wang; Jing Diao; La Xu; Chunlei Gai; Hongjun Liu; Danping Ma (Aquaculture International, 2021)

Comparison of the Economic Performances of Three Sulphur Oxides Emissions Abatement Solutions for a Very Large Crude Carrier (VLCC) - Hongjun Fan; Huan Tu; Hossein Enshaei; Xiangyang Xu; Ying Wei (Journal of Marine Science and Engineering, 2021)
Ship-source air pollutants, especially sulphur oxides (SOx), have a major impact on human health, the marine environment and the natural resources. Therefore, control of SOx emissions has become a main concern in the maritime industry. The International Maritime Organization (IMO) has set a global limit on sulphur content of 0.50% m/m (mass by mass) in marine fuels which has entered into effect on 1 January 2020.To comply with the sulphur limits, ship owners are facing the need to select suitable abatement solutions. The choice of a suitable solution is a compromise among many issues, but the economic performance offers the basis for which ones are attractive to ship owners. Currently, there are three technologically feasible SOx abatement solutions that could be used by ships, namely, liquified natural gas (LNG) as a fuel (Solution A), scrubbers (Solution B) and low-sulphur fuel oil (LSFO) (Solution C). To compare the economic performances of the mentioned three solutions for a newbuilding very large crude carrier (VLCC), this paper proposes a voyage expenses-based method (VEM). It was found that, within the initial target payback period of 6 years, Solution A and C are more expensive than Solution B, while Solution C is more competitive than Solution A. Five scenarios of target payback years were assumed to compare the trends of the three proposed solutions. The results show that Solution B maintains its comparative advantage. As the assumed target payback years becomes longer, the economy of Solution A gradually improves and the economics of Solution B and C gradually decline. A comparison between Solution A and C shows 6.5 years is a turning point. The advantage of Solution A is prominent after this payback period. In addition, the performance of a certain solution in terms of adaptability to the IMO greenhouse gas (GHG) emissions regulations is also a factor that ship owner need to consider when making decisions. In conclusion, when the IMO air pollutant regulations and GHG regulations are considered simultaneously, the advantages of using LNG are obvious.

Bilinear neural network with 3-D attention for brain decoding of motor imagery movements from the human EEG - Chen-Chen Fan; Hongjun Yang; Zeng-Guang Hou; Zhen-Liang Ni; Sheng Chen; Zhijie Fang (Cognitive Neurodynamics, 2021)

A new permeability predictive model based on NMR data for sandstone reservoirs - Hongjun Xu; Changxi Li; Yiren Fan; Falong Hu; Jun Yu; Jinyu Zhou; Changxue Wang; Chunmei Yang (Arabian Journal of Geosciences, 2020)

Decadal characteristics of the floating Ulva and Sargassum in the Subei Shoal, Yellow Sea - Jie Xiao; Shiliang Fan; Zongling Wang; Mingzhu Fu; Hongjun Song; Xiao Wang; Chao Yuan; Min Pang; Xiaoxiang Miao; Xuelei Zhang (Acta Oceanologica Sinica, 2020)

Geochemical characteristics and accumulated process of heavy crude oil of Chunguang oilfield in Junggar Basin, China - Yuanfang Fan; Lianfu Mei; Hongjun Liu (Journal of Earth Science, 2016)

Isolation and Characterization of a Novel Noncoding RNA from Nickel-Induced Lung Cancer - Jing Zhang; Yang Zhou; Youjun Wu; Lin Ma; Yingying Fan; Xuan Kang; Hongjun Shi; Jun Zhang (Biological Trace Element Research, 2012)

Identification of Differentially Expressed Genes in Lung Tissues of Nickel-Exposed Rats Using Suppression Subtractive Hybridization - Jing Zhang; Jun Zhang; Yingying Fan; Lihong Liu; Mengjie Li; Yang Zhou; Zhihua Shao; Hongjun Shi; Ying Wang (Biological Trace Element Research, 2011)

The expression of Na, K-ATPase in Litopenaeus vannamei under salinity stress - Hongyan Sun; Lvping Zhang; Chunhua Ren; Chang Chen; Sigang Fan; Jian Jun Xia; Hongjun Lin; Chaoqun Hu (Marine Biology Research, 2011)